The Mediterranean Diet A Clinician's Guide for Patient Care - Zacharias, Eric (Springer New York : Imprint: Springer, 2012)
Over the past several years there has been increasing information in the medical literature regarding the health benefits of a Mediterranean diet.  Clinicians may not be informed on advances in nutrition, and studies have demonstrated that they do not spend much time discussing food as a means for promoting health with patients.  The Mediterranean Diet: A Clinician's Guide for Patient Care is an essential new volume that serves as an update and a reference for clinicians on the Mediterranean diet.  Specific diseases and the effects the Mediterranean diet have on them are outlined.  Diseases and conditions that are outlined include heart disease, stroke, Alzheimer's, depression, cancer, allergies, asthma, arthritis and diabetes.  A detailed analysis of the specific nutrients in a Mediterranean diet and the food groups containing them is also included.  A useful guide containing daily meal plans and an extensive recipe section prepared by a team of dieticians can be found in the patient resources section.  The Mediterranean Diet: A Clinician's Guide for Patient Care provides a useful summary of the constituent components and health benefits of a Mediterranean diet to health professionals.